Policy Implementation of Government Regulation Number 12 of 2021 on Housing and Settlement Area Management - Hamirul, H; Elsyra, Nova; Permana, Ipik; Poiran, P (Universitas Muhammadiyah Surakarta, 2023)
Government Regulation Number 12 of 2021 on housing and settlement area management, Article 17, paragraph 5 explains that the technical standards for implementing housing construction must be met, which consist of standard facilities, infrastructure, and utilities to make housing development livable. This research aims to determine the implementation of Government Regulation Number 12 of 2021 on managing housing and settlement areas in the Bungo Regency. The research method was a descriptive method with a qualitative approach. The research population consisted of the Housing and Settlement Areas (Perkim) Office of Bungo Regency, the developer, and the people living in the housing, with a total sample of 11 people using incidental and purposive samplings. The research results revealed that the implementation of housing and settlement areas in the Bungo Regency had been carried out by related parties, in this case, the Bungo Regency housing and settlement service and the developer. However, they have not been optimal yet because the implementation of housing development was still related to providing facilities, infrastructure, and utilities that had not been fulfilled. It was because there was still a lack of public knowledge regarding technical standards for housing management, irresponsible or indifferent attitudes from developers after many people lived in the housing area, and a lack of socialization and application of sanctions for developers who violated housing development regulations.